Optically detected magnetic resonance in nanodiamonds with single nitrogen-vacancy defects - CORONEL SANCHEZ, Edwin Danelli (2016)
The control of the radiation-matter interaction, in our case of photons with quan- tum single emitters, as the nitrogen-vacancy (NV) defect in nanodiamonds, is crucial in the process of nano-devices fabrication. This is achieved taking advantage of the latest advances of the nano-optics to increase the interaction with single emitters for which ade-quate tools for precise interaction control has been developed. In this dissertation, we use a home-made inverted optical confocal microscope and coherent manipulation of spin states to study single NV defect in nanodiamonds. The NV defect in nanodiamonds presents optical properties that depend on the spin state of its optically active electrons, which makes them interesting for applications in nanomagnetometry, quantum informa- tion processing and nanobiothermometry. In particular, the negatively charged NV defect (NV-) exhibits single photon emission and long coherence times even at room tempera- ture. Furthermore, it has a paramagnetic ground state and can be optically polarized and read out, in an experimental technique known as Optically Detected Magnetic Resonance (ODMR). In this technique, the intensity of the fluorescence emitted by a nanodiamond depends on the spin configuration of the electronic ground state, from which an electronic transition is excited. In order to study these defects, nanodiamonds were deposited on a photolitographically structured antenna on a coverslip by spin coating and placed on the microscope. The microscope allows to both, the detection of the fluorescence and its exci- tation, by a CW laser emitting at 532 nm. The fluorescence emitted by the nanodiamond is centered around 650 nm with a zero phonon line at 637 nm. The collected fluores¬cence is sent to two avalanche photodiodes (APDs), that are in a configuration known as Hanbury-Brown and Twiss (HBT) interferometer. In it, we can verify whether the col- lected emission comes from an individual emitter, analyzing the second order correlation function g(2)(r): if g(2)(r) < 0.5 we have an emission from single photons generated by a single NV- defect in diamond. Working whit single emitter we could radiate a microwave field over the nanodiamond, which allows us to determine the resonance frequency for spin transitions in the ground state. At resonance one observes a drop in the fluorescence emitted by the nanodiamond. We explore the fact that the resonance frequency of the spin transition depends on the local magnetic field to measure the Zeeman effect gener- ated by the magnetic field of a permanent magnet (NdFeB). Finally, we realized coherent manipulation via an appropriate sequence of pulses of microwave and laser, observing Rabi oscillations. Thus, we can measure the inhomogeneous coherence time (T2*) given by the damping of Rabi oscillations.